Synthesis, Characterization, and Study of Liquid Crystals Properties of New Five Heterocyclic Compounds - Amine, Adiba K.; Karam, Nisreen H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
This work includes the synthesis and characterization of new compounds that contain 5H-thiazolo[4,3-b][1,3,4] thiadiazol united in multiple steps, starting with the synthesis of the aldehyde compound [I] by reaction chloro ethyl acetate with 4-hydroxybenzaldehyde in the presence of ethanol and potassium carbonate, followed by reactions with thiosemicarbazide, mercapto acetic acid in sulphuric acid to produce compound [II] then reflux compound [II] with hydrazine hydrate to product compound [III], after that reaction the later compound with n-alkoxybenzaldehyde [IV]n and a few drops of piperidine in THF as a solvent to produce new Schiff᾽s-bases compounds contain 5H-thiazolo [4,3-b] [1,3,4] thiadiazol unite [V]n, FTIR and 1HNMR spectroscopy were used to analyze the compounds, a polarized optical microscope (POM) and differential scanning calorimetry (DSC) were used to examine the characteristics of the liquid crystals. In the Smectic A (SmA) and nematic phases, liquid crystal characteristics are present in all compounds [V]n. In addition to the nematic phase, all compounds [V]n showed enantiotropic dimorphism in the SmA phase. It was discovered that compounds [V]n with 5H- thiazole [4,3-b] [1,3,4]thiadiazol unit, the rigid-rod core of Schiff bases, and the formation of a supramolecular hydrogen bond between the derivatives [V]n had liquid crystallinity, depending on the chain length of the alkoxy group as a terminal substituent.